Pengaruh Metode Penugasan Terhadap Hasil Belajar Tari Siswa Di Kelas VII SMPN 21 Batanghari Provinsi Jambi - Rikeu Farhah; Susmiarti Susmiarti (SENDRATASIK UNP, 2022)
This research proposes a formulation of the problem that is "How does the effect of assignment methods on the results of dance learning in Class VII SMPN 21 Batanghari Jambi Province". So that the purpose of the research is to prove and explain that the use of assignment methods affects the results of dance learning in Class VII of SMPN 21 Batanghari Jambi Province. This type and approach of research is quantitatively short-shortening quasi-experiments, with research designs that only control the test results at the end (posttest only control of design). The research population was in all students of class VII of State Junior High School 21 Batanghari which amounted to 121 students. The sample was in two classes, in 30 class VII-B, called The Experiment Class and 30 VII-C students, called the Control class. A simple sample cluster sampling is the sampling technique. After the test was conducted, it was known that the average test score of the end test of the experimental class and the control class before being tested and the t-test was 84.00 versus 80.50. After these two average scores were tested again using the t-Test formula in SPPS v16 at a degree of freedom of 29 and alpha level of 0.05%, it was found that the t-count value = 3,672. If this t-count value is cooled by the t-table as listed in Table T, the t-table value is 1.69913. This means that the t-count value is greater than the t-table. Test results stated H1 was accepted, and H0 was rejected. The conclusion is that the application of assignment methods affects the difference in learning outcomes to be higher in dance learning in Class VII SMPN 21 Batanghari Jambi Province.